New Media Professions: Analysis of the Reality and Academic Training Requirements A Field Study on a Sample of Professors in Media and Communication Sciences at Algerian Universities - khenti , Merwa; himeur, Saida. (Journal of Social Sciences and Humanities, 2025)
This research paper aims to examine the current state of new media professions in academic media training and the requirements for such training. Media professions are the cornerstone of media activities and form the basis for the field in general across its various domains. No field can exist without the presence of professions and roles it relies on. Media professions have been significantly impacted by the ongoing revolution in information and communication technologies, technological advancements, and the emergence of the digital environment. All these changes have led to the rise of digital media, closely connected to the internet and modern technological techniques, which has directly contributed to the emergence of new media professions that have spread widely in recent years. These new professions are practiced according to the indicators of the digital environment, in a manner completely different from traditional media professions. Through our study of this topic, using a descriptive methodology with data collection tools such as observation and interviews, and relying on a purposive random sample consisting of 18 media and communication professors, we found that new media professions emerged due to various reasons and have significant benefits for the development of the media field. The training process for these professions requires numerous requirements, such as the development of curricula, training programs, and educational materials that align with digital media and the new professions that have emerged with its spread. Additionally, it is essential to provide facilities equipped with modern technological and digital tools, which will enhance the training process, a crucial aspect for practicing these professions.